Infrequent Air Contamination with Acinetobacter baumannii of Air Surrounding Known Colonized or Infected Patients - Rock, Clare (Infect Control Hosp Epidemiol, 2015)
Using a validated air sampling method we found Acinetobacter baumannii in the air surrounding only 1 of 12 patients known to be colonized or infected with A. baumannii. Patients’ closed circuit ventilator status, frequent air exchanges in patient rooms and short sampling time may have contributed to this low burden.